Caracterização do lodo gerado em estações de tratamento de esgoto sanitário da região metropolitana de Fortaleza visando sua utilização na agricultura - Bezerra, Keyve Mayane (2014)
The high production of sludge in large urban centers, coupled with the need for proper disposal, has generated serious environmental problems in the country. Most of sludge produced worldwide is intended for incineration, landfilling and agricultural use. Among the alternatives to reuse a viable technique is to use as organic fertilizer because the nutrients contained, making it an input with high economic value. The aim of this study was to characterize the sludge from the wastewater treatment plants located in the Metropolitan Region of Fortaleza, in order to reuse in agriculture and providing alternative routes to their final destination. Monthly samples of sludge were carried out in the period August to November 2013 After collection, the analysis of the parameters was performed: temperature, pH, total alkalinity, conductivity, alkalinity of Volatile Acids (AAV), Volatile Fatty Acids (VFA) , specific weight, moisture content, solids and nitrogen, total phosphorus, chemical oxygen demand (COD), and Total Coliform and Escherichia Coli and inorganic substances (heavy metals and some nutrients). The results indicate that the sludge contains nutrients such as nitrogen and phosphorus necessary for the growth of plants and may be used as a form of recycling in agriculture, providing an environmentally friendly target, provided that pass through a suitable treatment for the removal or reduction of pathogens before its application. All slurries exhibited stable for agricultural use, whereas in one study SV / ST ratio less than 0.70 was found. According to the concentration of heavy metals, they could be reused in agriculture, as had lower values ​​compared with the limits established in legislation braseileira, but no restriction, just, septic sludge, due to the concentration range of zinc exceeds the maximum limit concentration permitted by CONAMA Resolution No. 375/2006.